"Structural Audit of an Old Building" (A Case Study). Issue 1 (November 2021) - Kondalkar, Ragini; Pitale, Nikhil H.; Dabhekar, K.R.; Mase, D.P.
Abstract: In India there are infinite old structures that are at the verge of damages. There are many buildings which have reduced their strength due to time passes, due to deterioration of concrete from structural element, due to development of cracks. The structure is a combination of load carrying members, damages in members cause failure of structure and it is harmful for living beings. To prevent old structure from failure the technique is adopted know as Non-Destructive Testing (NDT). With the help of non-destructive testing auditing of an old structure is get easier. NDT examine the total health of an infrastructure in order to check strength and stability of building. NDT is a bunch of various testing consist of Ultrasonic pulse velocity test (UPV), Rebound hammer test (RHT), Half-cell test, etc. Conducting NDT on building and analyzing testing result decide to repair building as per IS code, technique like grouting, Retrofitting, etc. to increase strength and stability of building. In this project structural has to be done on old structure which is situated at Nagpur. Audit done by NDT consist of Ultra-sonic pulse velocity test, Rebound hammer test, Half-cell test. After analyzing all test result including visual inspection it is found that structure need to repair and retrofitted to make it safe and stable for all static loadings. Column jacketing also provide to structure.